Sotrastaurin, a PKC inhibitor, attenuates RANKL‐induced bone resorption and attenuates osteochondral pathologies associated with the development of OA. Issue 15 (11th July 2020) - Pang, Cong; Wen, Liangbao; Qin, Haikuo; Zhu, Bikang; Lu, Xuanyuan; Luo, Shixing
Abstract: Osteoarthritis (OA) is a common degenerative disease that affects the musculoskeletal structure of the whole joint, which is characterized by progressive destruction of both articular cartilage and subchondral bone. Treatment of the bone pathologies, particularly osteoclast‐mediated subchondral bone loss in the early stages of OA, could prevent subsequent cartilage degeneration and progression of OA. In the present study, the PKC inhibitor, Sotrastaurin, was found to inhibit RANKL‐induced osteoclast formation in vitro in a dose‐ and time‐dependent manner. In particular, SO exerted its anti‐osteoclastic effect predominantly at the early stages of RANKL stimulation, suggesting inhibitory effects on precursor cell fusion. Using mature osteoclasts cultured on bovine bone discs, we showed that SO also exerts anti‐resorptive effects on mature osteoclasts bone resorptive function. Mechanistically, SO attenuates the early activation of the p38, ERK and JNK signalling pathways, leeding to impaired induction of crucial osteoclast transcription factors c‐Jun, c‐Fos and NFATc1. We also showed that SO treatment significantly inhibited the phosphorylation of PKCδ and MARCKS, an upstream regulator of cathepsin K secretion. Finally, in animal studies, SO significantly alleviates the osteochondral pathologies of subchondral bone destruction as well as articular cartilage degeneration following DMM‐induced OA, markedly improving OARSI scores. The reduced subchondral bone loss was associated with marked reductions in TRAP(+) osteoclasts in the subchondral bone tissue. Collectively, our data provide evidence for the protective effects of SO against OA by preventing aberrant subchondral bone and articular cartilage changes. Thus, SO demonstrates potential for further development as an alternative therapeutic option against OA.